Judaism and Hellenism reconsidered - Feldman, Louis H. (Supplements to the Journal for the Study of Judaism, 2006)
This book is a collection of 26 previously published articles, with a number of additions and corrections, and with a long new introduction on "The Influence of Hellenism on Jews in Palestine in the Hellenistic Period." The articles deal with such subjects as "Homer and the Near East," "The Septuagint," "Hatred and Attraction to the Jews in Classical Antiquity," "Conversion to Judaism in Classical Antiquity," "Philo, Pseudo-Philo, Josephus, and Theodotus on the Rape of Dinah," "The Influence of the Greek Tragedians on Josephus," "Josephus' Biblical Paraphrase as a Commentary on Contemporary Issues," "Parallel Lives of Two Lawgivers: Josephus' Moses and Plutarch's Lycurgus," "Rabbinic Insights on the Decline and Forthcoming Fall of the Roman Empire."